Evaluasi Jaringan Pipa Minyak Lepas Pantai Guna Optimasi Produksi Area "WK-1" Lapangan "R" - Alfan Khoirul Umam; Hadziqul Abror; Riska Laksmita Sari (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Field "R" is an old field located in the South East Sumatra Block. The pipeline network in Area "WK-1" in field "R" has 8 platforms namely the Rama-B, Rama-D, Rama-I, S.W. Wanda-A, Wanda-A, N. Wanda-A, Gita-A, and Rama-C. There are 31 producing wells through the 8 platforms. The purpose of this research is to create a piping network model for Area "WK-1" Field "R", identify optimal or non-optimal conditions for pipelines through simulation results and matching on the pipeline network model, identify whether bottlenecking problems occur in the piping network Area "WK-1" Field "R" using the matching results on the piping network model so that the location of pipes and nodes with fluid problems can be found precisely, and carry out production optimization simulations to increase production rates oil in Area "WK-1" Field "R". Production well modeling and pipeline network modeling using a multiphase steady-state production simulator application, the models that have been made will be validated matching against actual conditions. From the results of matching the pipe network model, an analysis of pipe problems that can occur such as bottlenecks is carried out. From the network simulation results, it can be seen that there is bottlenecking on the pipeline in Area "WK-1" Field "R". This is due to the condition of the pipeline network which has been operating for quite a long time since 1974. From the simulation results, there are 2 optimization scenarios, the production capacity of each well can still be increased and the total rate of oil production increases. In the first scenario, the Bean Size setting on the Choke is 48.92 BOPD with an average increase of 1.55%. Whereas in the second scenario, by opening the pressure limits at the wellhead points, the yield is 583.25 BOPD with an average increase of 16.13%.